Hubungan Antara Kerjasama Dengan Perilaku Pengasuhan Orang Tua Dalam Mengelolah Anak Sulit Makan Di TK Stella Maris Bitung : The Relationship Between Collaboration and Parenting Behavior in Managing Children Who Have Difficulty Eating at Stella Maris Bitung Kindergarten - Lefteuw, Maria Stella Maris (Dohara POAJ, 2023)
Introduction: Pre-school children are those aged between 3-6 years. Children at preschool age usually experience psychological development to become toddlers who are more independent, autonomous, able to interact with their environment, and can express their emotions more. In addition, children of this age also tend to like to explore new things. The developmental characteristics that are formed also influence children's eating patterns (Hidayat 2013 in Katiandagho et al 2016). Difficulty eating can occur due to several things, including cooperation and parenting behavior of parents to children. Parents in the family have an important role in childcare practices. The participative role of parents determines the quality of child care and its influence on children (Mohamad Mahpur, Koentjoro, and Subandi 2021). Methods: Quantitative with a research design using a cross-sectional approach the sample in this study were all parents of students at Stella Maris Bitung Kindergarten as many as 45 parents, the sampling technique was total sampling. Results: Parental cooperation resulted in the collaboration of 31 (69,9%) respondents, while respondents who did not cooperate were 14 (31,1%) respondents. while parents with good parenting behavior were 31 (68,9%) respondents, while respondents with poor parenting behavior were 14 (31,1%) respondents. Hypothesis testing using chi-square obtained a p-value of 0,000 (P <0,05). Discussion: There is a significant relationship between parental cooperation and parenting behavior in managing children with difficulty eating at Stella Maris Bitung Kindergarten.